Reflecting Collectively on Histories of Black Montreal - Rochat, Désirée; Williams, Dorothy; Belony, Lyns-Virginie; Currie-Williams, Kelann; Theliar-Charles, Kessie; Dumais, Samia (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2025)
Black community members in and of Montreal have always worked to document and transmit their histories. Over the years, constellations of women and men spread histories that anchored Blackness in the city, while anchoring the city in wider Black networks. By circulating historical, methodological, and archival knowledge, they forged a Black Montreal historical tradition that continues to be carried forward. The contributors to this special section of the Journal of the Canadian Historical Association, comprising three generations of Black historians based in Montreal, are very much part of this wider tradition. The special section comprises an introduction, three articles, and an interview. This introduction is based on a recorded conversation between the contributors and offers reflections on what it means to think about and transmit histories of Black Montreal collectively.